Mapping mountains: vegetation in the Himalaya - Schweinfurth, Ulrich (GeoJournal, 1992)
The author deals with the vegetation of the Himalayas taking his 1957 map as basis of the presentation. This map by way of vegetation first opened insigh into the hitherto unknown landscape structure of the mountain system, thereby revealing, for instance, the phenomeon of the inner valleys and the climatically dry valleys, in particular as well as the areas vegetationwise still unknown. Progress in our knowledge of the vegetation in the Himalayas since publication of the 1957 map is carefully recorded showing, above all, the advancement of our knowledge in Nepal since. In contrast to expectations, research was unable to concentrate on all the gaps in our knowledge as demonstrated on the 1957 map owing to political conditions prevailing.